Pharmacist- versus physician-acquired medication history: a prospective study at the emergency department. Issue 5 (1st July 2010) - De Winter, Sabrina; Spriet, Isabel; Indevuyst, Christophe; Vanbrabant, Peter; Desruelles, Didier; Sabbe, Marc; Gillet, Jean Bernard; Wilmer, Alexander; Willems, Ludo
Abstract : Background: Recent literature revealed that medication histories obtained by physicians and nurses are often incomplete. However, the number of patients included was often low. Study objective: In this study, the authors compare medication histories obtained in the Emergency Department (ED) by pharmacists versus physicians and identify characteristics contributing to discrepancies. Methods: Medication histories were acquired by the pharmacist from patients admitted to the ED, planned to be hospitalised. A structured form was used to guide the pharmacist or technician to ensure a standardised approach. Discrepancies, defined as any difference between the pharmacist-acquired medication history and that obtained by the physician, were analysed. Results: 3594 medication histories were acquired by pharmacy staff. 59% (95% CI 58.2% to 59.8%) of medication histories recorded by physicians were different from those obtained by the pharmacy staff. Within these inaccurate medication histories, 5963 discrepancies were identified. The most common type of error was omission of a drug (61%; 95% CI 60.4% to 61.6%), followed by omission of dose (18%; 95% CI 17.6% to 18.4%). Drugs belonging to the class of psycholeptics, acid suppressors and beta blocking agents were related to the highest discrepancy rate. Acetylsalicylic acid, omeprazole and zolpidem were most commonly forgotten. Conclusion: This large prospective study demonstrates that medication history acquisition is very often incomplete in the ED. A structured form and a standardised method is necessary. Pharmacists are especially suited to acquire and supervise accurate medication histories, as they are educated and familiar with commonly used drugs.